البلدان المغاربية وتحديات الاقتصاد الجديد. - لحمر, عباس (جامعة الوادي - University of Eloued, 2018)
ارتبط الاقتصاد الجديد بتكنولوجيا المعلومات والاتصالات، حيت تكون فيه المعلومات ركيزة جديدة وتحدي تنافسي للمؤسسات والاقتصاديات، ويتطلب هذا الاقتصاد بيئة رقمية عالية وبنية تحتية قوية، وتلعب فيه المعرفة دورا أساسيا في تحريك الاقتصاد. لقد بدلت البلدان المغاربية جهودا معتبرة ومبادرات عديدة لتحسين بيئتها الرقمية وتوفير فرص النفاد إلى تكنولوجيا المعلومات والاتصالات، ومن هنا جاءت هذه الورقة البحثية للوقوف على ملامح الاقتصاد الجديد والدور الاستراتيجي لتكنولوجيا المعلومات والاتصالات، بالإضافة إلى دراسة واقع البيئة الرقمية في البلدان المغاربية ومقومات اندماجها في الاقتصاد الجديد والتقليص من الفجوة الرقمية الموجودة. The new economy has been associated with the information and communication technology, where information is an important pillar and a competitive challenge for enterprises and economies. This economy requires in a high digital environment and a strong infrastructure, in which knowledge plays a key of the economy. The Maghreb countries have made considerable efforts and initiatives to improve their digital environment and provide access to ICTs. This research aims is to identify the features of the new economy and the strategic role of ICT, as well as to study the reality of the digital environment in the Maghreb countries and their integration into the new economy and reduce the existing digital divide.
Maghreb countries and the challenges of the new economy
مقال
Keywords: الاقتصاد الجديد؛ تكنولوجيا المعلومات والاتصالات؛ البيئة الرقمية؛ شبكة الانترنت؛ الهاتف النقال؛ الفجوة الرقمي; New economy; ICT; Digital environment; Internet; Mobile phone; Digital divide